2022
DOI: 10.1111/pim.12939
|View full text |Cite
|
Sign up to set email alerts
|

The effect of helminth infection on vaccine responses in humans and animal models: A systematic review and meta‐analysis

Abstract: Vaccination has potential to eliminate infectious diseases. However, parasitic infections such as helminths may hinder vaccines from providing optimal protection. We reviewed existing literature on the effects of helminth infections and their treatment on vaccine responses in humans and animals. We searched literature until 31 January 2022 in Medline, EMBASE, Global health, Scopus, and Web of science; search terms included WHO licensed vaccines and human helminth types. Standardized mean differences (SMD) in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…Previous studies of other vaccines discussed in the preceding text suggest cause for concern on effects of helminth infections on COVID-19 vaccination programs. There is growing evidence that vaccine efficiency is reduced where helminth infections are prevalent, with reduced efficiencies shown for BCG, tetanus, diphtheria, measles, and malaria vaccines [ 13 ]. It has been reported helminths reduce Th1- and Th17-induced antiviral activity and vaccination efficacy [ 74 ].…”
Section: Do Helminth Infections Interfere With Covid-19 Vaccine Effic...mentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies of other vaccines discussed in the preceding text suggest cause for concern on effects of helminth infections on COVID-19 vaccination programs. There is growing evidence that vaccine efficiency is reduced where helminth infections are prevalent, with reduced efficiencies shown for BCG, tetanus, diphtheria, measles, and malaria vaccines [ 13 ]. It has been reported helminths reduce Th1- and Th17-induced antiviral activity and vaccination efficacy [ 74 ].…”
Section: Do Helminth Infections Interfere With Covid-19 Vaccine Effic...mentioning
confidence: 99%
“…Epidemiological surveys have found that mass vaccination is sometimes less effective than expected, especially in developing countries [ 7 , 8 ].The century-old Bacille Calmette-Guérin (BCG) and measles vaccines are reported to be less effective in Africa and Southeast Asia than in developed countries [ 9 , 10 ]. The failure of vaccination to achieve the desired protective effect is not only related to technical reasons, such as vaccine quality and vaccination method, but also related to environmental exposure, one of which is the prevalence of helminth infections in many regions around the world [ 11 , 12 , 13 , 14 ]. The World Health Organization (WHO) estimates that helminth infections affect more than a quarter of the population, and more than 880 million children require treatment for these parasite diseases, including approximately 350 million in the African region [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To illustrate the utility of the proposed unsupervised title and abstract screening for systematic reviews, data from two completed systematic reviews will be used. A systematic review assessing the effect of helminths on vaccines response (Case study 1: the helminths data)a planned systematic review for which full-text review of documents has been completed [25] and from a published systematic review on the effectiveness of therapies for Wilson disease (Case study 2: Wilson disease data) [26] will be analysed. For both case studies, information on initial records identified through database search and results after manual title and abstract screening is available.…”
Section: Introductionmentioning
confidence: 99%